Robotic pancreatic resection. Personal experience with 105 cases - MACHADO,MARCEL AUTRAN CESAR (2020)
ABSTRACT Objective: the first robotic pancreatic resection in Brazil was performed by our team in 2008. Since March 2018, a new policy prompted us to systematically employ the robot in all minimally invasive pancreatic surgery. The aim of this paper is to review our experience with robotic pancreatic resection. Methods: all patients who underwent robotic pancreatic resection from March 2018 through December 2019 were identified. Descriptive data were collected. Preoperative variables included age, sex, and indication for surgery. Intraoperative variables included operative time, bleeding, blood transfusion. Results: 105 patients underwent robotic pancreatectomy. Median age was 60.5 years old. Fifty-five patients were female. 51 patients underwent robotic pancreatoduodenectomies, 34 distal pancreatectomy. Morbidity was 23.8%, mainly related to postoperative pancreatic fistula and one death occurred (mortality of 0.9%). Three patients (2.8%) were converted to open surgery. Four patients had delayed gastric emptying and two presented bleeding. Twenty-four patients had pancreatic fistula that was treated conservatively with late removal of the pancreatic drain. No patient required percutaneous drainage, reintervention or hospital readmission. Conclusions: the robotic platform is useful for the reconstruction of the alimentary tract after pancreatoduodenectomy or after central pancreatectomy. It may increase the preservation of the spleen during distal pancreatectomies. Pancreas sparing techniques, such as enucleation, resection of uncinate process and central pancreatectomy, should be used to avoid exocrine and/or endocrine insufficiency. Robotic resection of the pancreas is safe and feasible for selected patients. It should be performed in specialized centers by surgeons with experience in both open and minimally invasive pancreatic surgery.